Tax audits: definition and methods. (Journal of Economic Research & Business Administration, 2016)
The article reveals information about the tax audit. Under the audit refers to the independent audit of the accounting statements of the audited entity for the purpose of expressing an opinion on reliability of such reporting. However, the presence of such reporting of a number of tax figures that are generated outside of accounting, and the necessity of their proof in the audit demanded from the auditors of new knowledge and experience. Still not defined the place of tax audit in the structure of services rendered by auditing organizations and individual auditors. So the problem of tax audit lies in the fact that legally this type of audit is not fixed. The article reveals the essence of the tax audit, determined by its position in the control system in General and in the modern system of the Kazakhstan audit in particular, given the definition of the tax audit, formulated its subject, method, functions and also identifies the relationship of the tax audit of efficiency of economic activity.
Keywords: Audit; tax audit; audit services; audit practice; tax risks